Pemanfaatan Google Meet dalam Pembelajaran IPS pada Masa Pandemi di SMP Negeri 7 Maluku Tengah - Maya Widya Serang; Merryl Pelamonia; Silvia Manuhuttu (Jurnal Pendidikan Ekonomi, 2025)
This study aims to analyze the use of the Google Meet application as a learning medium for Social Studies (IPS) during the COVID-19 pandemic at SMP Negeri 7 Malteng. A qualitative descriptive approach was employed, with data collected through in-depth interviews, observation, and documentation. The findings reveal that Google Meet provides ease of access, time flexibility, and the ability to present relevant visual materials such as maps and infographics. Teachers are able to deliver content directly and interactively; however, the effectiveness of learning largely depends on infrastructure readiness, the digital competence of both teachers and students, and the instructional strategies applied. Challenges encountered include limited two-way interaction, technical issues such as connectivity disruptions, and low student motivation. In the context of Social Studies, which requires dialogue and contextual understanding, the use of Google Meet alone is not fully optimal without integrating additional learning media. This study contributes to the development of adaptive online learning strategies and provides policy recommendations for more inclusive and collaborative technology-based education